Integration of the Alexa assistant as a voice interface for robotics platforms - Hidalgo-Paniagua, Alejandro; Millán-Alcaide, Andrés; Bandera-Rubio, Juan Pedro; Bandera-Rubio, Antonio Jesús (My University, 2019)
Virtual assistants such as Cortana or Google Assistant are becoming familiar devices in everyday environments, where they are used to control real devices through natural language. This paper extends this application scenario, and it describes the use of the Alexa assistant from Amazon through an Echo dot device to drive the behaviour of a robotic platform. The paper focuses on the description of the technologies employed to set such ecosystem. Significantly, the proposed architecture is based, from the remote server to the on-board controllers, in LowEnergy (LE) hardware and a scalable software platform. This approach will ease programmers integrating different platforms, e.g. mobile-based applications to control robots or home-made devices.
Keywords: Informática - Aplicaciones; Robótica; Virtual assistant; Human-robot interface; Voice commanding